Repeatability of corneal biomechanics waveform signal parameters derived from Ocular Response Analyzer in children. Issue 5 (October 2021) - Wan, Kin; Cheung, Sin Wan; Wolffsohn, James Stuart; Cho, Pauline
Abstract: Purpose: To investigate the repeatability of waveform signal parameters, measured with the Ocular Response Analyzer (ORA), in children. Methods: Two sets of ORA measurements, with a 10-min break between them, were performed on children, aged six to <11 years old, either wearing single-vision spectacles (SVS) or orthokeratology (ortho-k) lenses. Intraclass correlation coefficients (ICCs) were used to assess agreements between two sets of measurements (37 waveform signal parameters). Bland-Altman (BA) plots were used to further analyse waveform signal parameters which had ICC 95 % confidence interval (95 % CI) between 0.50 to >0.90 (regarded as moderate to excellent agreement). Results: A total of 30 participants [15 SVS, 15 ortho-k (3.6 ± 2.4 months)] completed the study. Since no significant between-group differences were detected in demographic data (p > 0.28) and all waveform signal parameters (p > 0.05), data from the two groups of participants were pooled for the analysis of repeatability. Six parameters, h2, h21, p1area, p1area1, p2area, and p2area1, achieved ICCs (95 % CI) of 0.82−0.85 (0.61−0.93). The mean (SD) of these six parameters were 372 (91), 248 (61), 4077 (854), 1762 (399), 2359 (670), and 1020 (300), respectively. Bland-Altman plots and 95 % limits of agreement (95 % LoA) showed considerable agreement for all six parameters, the mean difference (95 % LoA) were -3 (-101 to 94), -2 (-67.56–62.70), 111 (-723 to 946), 102 (-334 to 539), 25 (-718 to 768), and -3 (-350 to 343), respectively. Conclusions: Six waveform signal parameters (h2, h21, p1area, p1area1, p2area, and p2area1), which represent or are related to the areas under the waveform at the peaks in the signal, had moderate to excellent agreement in children. Results of the current study provides fundamental information for further studies on the potential clinical application of these waveform signal parameters in children.